Pengaruh Perceived Ease of Use dan Promotion pada Layanan Aplikasi GoPay terhadap Consumptive Behavior Mahasiswa S1 Fakultas Ekonomi 2022 Universitas Negeri Jakarta - Andreas Pandu Prasetya; Alfin Lazuardy Nur; Yusrizal Abdul Khamid; Muhammad Zahraan Sakti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the influence of Perceived Ease of Use and Promotion on the use of the GoPay application towards the Consumptive Behavior of undergraduate students in the Faculty of Economics at Universitas Negeri Jakarta. In the digital era, electronic wallets like GoPay have become popular due to their ease of use and various attractive promotions offered. This study employs a quantitative method by collecting data through a survey questionnaire distributed to 50 students who are GoPay users. Multiple linear regression analysis was used to test the research hypotheses. The results indicate that both Perceived Ease of Use and Promotion have a positive and significant effect on Consumptive Behavior among students. Perceived Ease of Use has an effect of 0.309, while Promotion has an effect of 0.319 on Consumptive Behavior. These findings confirm that ease of use and effective promotions can enhance Consumptive Behavior among students. This research is expected to provide insights for more prudent financial management among students and more effective promotional strategies for electronic wallet service providers.